A phosphorus-carbon composite material and its preparation method and application

By using phosphorus-carbon composite materials in lithium-ion batteries, graphite materials are used to load elemental red phosphorus and use fast ion conductor composite as shell layer to form a core-shell structure, the volume effect and low conductivity of elemental phosphorus in lithium-ion batteries are solved, and efficient and stable electrochemical performance and safety are achieved.

CN119742346APending Publication Date: 2025-04-01HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936268.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Elemental phosphorus has severe volume effects and low conductivity in lithium-ion batteries, resulting in the inability to achieve commercialization of material properties and safety problems.

Method used

The core is constructed by using phosphorus-carbon composite materials to load the elemental red phosphorus through graphite material, and the fast ion conductor composite is used as the shell layer to finally form a core-shell structure to regulate the compressive strength of the material.

Benefits of technology

The volume effect of elemental phosphorus is suppressed, lithium-ion evolution phenomenon is avoided, conductivity and low-temperature performance are improved, and the structural stability and electrochemical performance of the material are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211595270000141
    Figure BDA0005211595270000141
  • Figure BDA0005211595270000151
    Figure BDA0005211595270000151
  • Figure BDA0005211595270000181
    Figure BDA0005211595270000181
Patent Text Reader

Abstract

The present application discloses a phosphorus-carbon composite material and its preparation method and application, which belongs to the field of battery technology. The material uses graphite as a matrix to load elemental red phosphorus and construct a core, and uses a fast ion conductor as a shell layer of the core to finally form a core-shell structure. At the same time, the compressive strength of the material is regulated within a specific range, which can not only achieve the ideal suppression of the elemental phosphorus volume effect, avoid safety problems caused by lithium precipitation when it is used in lithium-ion batteries, but also achieve excellent first efficiency and cycle stability under the premise of ensuring a high gram capacity, and can also achieve a high level of charge and discharge performance in a low temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a phosphorus-carbon composite material and a preparation method and application thereof. Background Art

[0002] The theoretical specific capacity of elemental phosphorus is as high as 2500mAh / g, and it is widely available and inexpensive. In theory, it is a popular choice for negative electrode materials of new-generation lithium-ion secondary batteries. However, elemental phosphorus has a serious volume effect in the actual charging and discharging process, with a high expansion ratio, which is highly destructive to the SEI film formed on the surface of the material, a high degree of active lithium loss, and even damage to the pole piece, leading to lithium precipitation. In addition, the material has poor conductivity, so its comprehensive performance cannot achieve a commercial product level similar to that of existing graphite materials.

[0003] In order to overcome the volume effect and low conductivity problems of elemental phosphorus, people have tried to modify it by doping and coating with graphite materials with good buffering properties and high conductivity, but the actual effect is not significant, and it may also cause other negative effects such as lower initial efficiency of the product, lower charge and discharge capacity, and weakened low-temperature performance. Summary of the invention

[0004] The purpose of the present application is to overcome the shortcomings of the prior art and provide a phosphorus-carbon composite material, which uses graphite as a matrix to load elemental red phosphorus and construct an inner core, and uses a fast ion conductor as a shell layer of the inner core to finally form a core-shell structure. At the same time, the compressive strength of the material is regulated within a specific range, which can not only achieve ideal suppression of the volume effect of elemental phosphorus and avoid safety problems caused by lithium precipitation when it is used in lithium-ion batteries, but also achieve excellent first efficiency and cycle stability while ensuring a higher gram capacity, and can also achieve a higher level of charge and discharge performance in a low temperature environment.

[0005] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a phosphorus-carbon composite material, comprising composite particles, wherein the composite particles include a core and a shell;

[0006] The core comprises graphite material and elemental red phosphorus;

[0007] The housing includes a fast ion conductor;

[0008] The fast ion conductor includes Li 3y Ce 14-3y Ti(PO4)6, 1≤y≤4;

[0009] The average particle size of the phosphorus-carbon composite material is 9 to 16 μm, and the powder compressive strength under a pressure of 5 T is 1.85 to 1.92 g / cm 3 .

[0010] As an embodiment of the present application, the average particle size of the inner core is 9 to 15 μm.

[0011] As an implementation scheme of the present application, the ratio of the thickness of the inner core to that of the outer shell is (500-1000):1.

[0012] As an implementation scheme of the present application, the mass ratio of the graphite material to the elemental red phosphorus in the inner core is 20:(1-3).

[0013] As an embodiment of the present application, the shell further includes a carbon material.

[0014] As an embodiment of the present application, the mass content of the fast ion conductor in the shell layer is 20-50%.

[0015] In a second aspect of the present application, the present application provides a secondary battery, wherein the secondary battery comprises a negative electrode plate, and the negative electrode plate comprises the phosphorus-carbon composite material described in the present application.

[0016] In a third aspect of the present application, the present application provides an electrical device, comprising the secondary battery, wherein the secondary battery serves as a power supply for the electrical device.

[0017] The beneficial effects of this application are:

[0018] The present application provides a phosphorus-carbon composite material, which uses graphite as a matrix to load elemental red phosphorus and construct an inner core, and uses a fast ion conductor as a shell layer of the inner core to finally form a core-shell structure. This material can not only achieve an ideal suppression of the volume effect of elemental phosphorus, avoiding safety problems caused by lithium precipitation when used in lithium-ion batteries, but also achieve excellent first efficiency and cycle stability while ensuring a high gram capacity, and can also achieve a high level of charge and discharge performance in a low temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the structure of composite particles in the phosphorus-carbon composite material of the present invention.

[0020] Figure 2 This is a scanning electron microscope image of the phosphorus-carbon composite material of the present invention.

[0021] Figure 3 This is a scanning electron microscope image of the phosphorus-carbon composite material of the present invention at a large magnification.

[0022] Figure 4 This is a scanning electron microscope image of the etched graphite material of the present invention. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0024] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0025] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0026] The present application is further described below with specific embodiments:

[0027] A phosphorus-carbon composite material, comprising composite particles, wherein the composite particles include a core and an outer shell;

[0028] The core comprises graphite material and elemental red phosphorus;

[0029] The housing includes a fast ion conductor;

[0030] The fast ion conductor includes Li 3y Ce 14-3y Ti(PO4)6, 1≤y≤4;

[0031] The average particle size of the phosphorus-carbon composite material is 9 to 16 μm, and the powder compressive strength under a pressure of 5 T is 1.85 to 1.92 g / cm 3 .

[0032] When the existing elemental phosphorus is used as the negative electrode material of lithium-ion batteries, the volume effect is very serious and the conductivity is poor, and the practicality is low. Some conventional doping and coating methods have very limited improvement on the material, and even weaken other properties of the material such as capacity, cycle performance, and low-temperature performance. In order to overcome this technical bottleneck, in the technical solution of this application, the inventor uses elemental red phosphorus as the capacity provider, first uses graphite material, which has high conductivity and high bonding strength as a load matrix, to match elemental red phosphorus to construct the core, and then uses a specific type of fast ion conductor to construct the shell, which together with the graphite material suppresses the volume effect of elemental red phosphorus and improves its conductivity and low-temperature performance; on the other hand, the design based on the configuration cannot guarantee the balance between the structural stability and electrochemical performance of the material when it is used as the negative electrode material of lithium-ion batteries. It is necessary to control the size of the composite particles in the material and the powder compressive strength of the overall material to achieve the expected performance improvement, and finally achieve the ideal first effect, cycle stability, and low-temperature performance, and still retain a high gram capacity.

[0033] In some embodiments, the average particle size of the phosphorus-carbon composite material is directly measured by a laser particle size analyzer to confirm the phosphorus-carbon composite material, and the average particle size is the particle size D of the phosphorus-carbon composite material. v50 .

[0034] In some embodiments, the powder compressive strength of the phosphorus-carbon composite material is tested by using a powder compaction density meter and setting a 5T pressure for 30 seconds to calculate the powder compressive strength: powder mass / powder volume after pressurization.

[0035] In some embodiments, the average particle size of the phosphorus-carbon composite material is in the range of one or any two of 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, 13 μm, 13.5 μm, 14 μm, 15 μm, and 16 μm.

[0036] In some embodiments, the average particle size of the core is 9 to 15 μm.

[0037] The size of the graphite material not only affects the load density when it is used as a matrix for elemental red phosphorus loading, but is also closely related to the dispersion uniformity and compressive strength of the material itself. In the technical solution of the present application, a graphite material close to the size of the composite particles of the overall material is selected as the core component, which can effectively regulate the structural stability of the particles, the dispersion of elemental red phosphorus, and the uniformity of the shell setting. All of them are maintained at a high level. If the setting is improper, it will not only cause the overall composite particle size to be too large or too small, and it will not be possible to guarantee its dimensional stability when used for lithium-ion battery negative electrode materials, and it may also cause the material to have poor circulation or low-temperature cycle performance due to component uniformity problems. When it is preferably within the above-mentioned size range, the volume effect of elemental red phosphorus in the obtained phosphorus-carbon composite material is better, and the uniformity between particles is better, and the electrochemical performance is better. In addition, although the size of the phosphorus-carbon composite particles is too small to achieve better ion / electronic conductivity efficiency, when preparing the pole piece, it is easy to roll overpressure, resulting in partial particle damage, red phosphorus exposure, and decreased electrochemical performance, while too large particles will cause the overall material to have a reduced ion / electronic conductivity efficiency.

[0038] In some embodiments, the average particle size of the core is in the range of one or any two of 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, 13 μm, 13.5 μm, 14 μm, and 15 μm.

[0039] In some embodiments, the ratio of the thickness of the inner core to that of the outer shell is (500-1000):1.

[0040] Specifically, the thickness ratio of the inner core to the outer shell is in the range of one or any two of 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1, 1000:1.

[0041] More specifically, the thickness of the outer shell is ≤100 nm.

[0042] More specifically, the thickness of the shell is in the range of one or any two of 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 30 nm, 40 nm, 50 nm, 55 nm, 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm.

[0043] More specifically, the shell has a thickness of 30-70 nm.

[0044] The selection of fast ion conductors is very critical. In the technical solution of the present application, based on the selection of specific fast ion conductors, the safety performance and cycle performance of the obtained composite particles, especially the cycle performance under low temperature environment, can be significantly improved. When the thickness of the shell layer constructed is preferably within the above range, the obtained product can further optimize the structural stability during the charge and discharge process, as well as the balance between charge and discharge capacity.

[0045] In some embodiments, the thickness of the inner core and the outer shell of the composite particles are confirmed in the following manner: the composite particles are positioned using a transmission electron microscope, and then the distribution diagram of the Li element, the Ce element or the Ti element is collected using EDS elemental analysis. Since these elements are only distributed in the shell layer of the composite particles, the thickness of the shell layer of the composite particles can be confirmed based on the transmission electron microscope image obtained from the EDS elemental analysis. At least 100 composite particles are measured using image processing software Image J, and each particle has 3 test points. The particle size and shell thickness of the composite particles at the 3 locations are calculated, the average value is calculated, and the thickness of the inner core is confirmed based on the difference between the particle size and the shell layer, and the average value is calculated as the final result.

[0046] In some embodiments, the mass ratio of the graphite material to the elemental red phosphorus in the inner core is 20:(1-3).

[0047] Specifically, the mass ratio of the graphite material to elemental red phosphorus is in the range of one or any two of 20:1, 20:1.2, 20:1.5, 20:1.8, 20:2, 20:2.2, 20:2.5, 20:2.8, and 20:3.

[0048] In some embodiments, the mass ratio of the graphite material to the elemental red phosphorus in the core is 20:(2-2.5)

[0049] As a key component of the inner core, the content ratio of elemental red phosphorus directly affects the actual capacity of the overall phosphorus-carbon composite material. The higher its content, the higher the gram capacity of the product will inevitably be, but the dimensional stability of the product will also decrease, the conductivity will also decrease, and the electrochemical activity will decrease. When the mass ratio of graphite material to elemental red phosphorus in the inner core is preferably within the above range, the overall performance of the resulting product will be better.

[0050] In some embodiments, the average particle size of the graphite material is 9 to 15 μm.

[0051] In the present application, a large-sized graphite material is selected as the loading matrix for loading elemental red phosphorus. Compared with a small-sized particle loading matrix, it can not only ensure the skeleton stability of the overall material structure, but also ensure that the elemental red phosphorus is evenly dispersed on the surface of the graphite material, and will not expand violently during the charge and discharge process due to local agglomeration, resulting in particle shedding or even piercing the diaphragm.

[0052] In some embodiments, the graphite material is etched.

[0053] Specifically, the phosphorus-carbon composite material controls the powder compressive strength by adjusting the etching degree of the graphite material, and the etching treatment is an alkaline solution etching treatment.

[0054] Compared with traditional carbon materials, graphite materials have higher hardness, better structural strength, and high initial compressive strength. After etching, the low-crystalline areas on its surface will be converted into partial micro-mesopores, providing load sites for elemental red phosphorus, and the compressive strength of the material will be further improved. In the above case, when elemental red phosphorus expands during the charging and discharging process, the buffering effect of graphite materials is better, which can effectively ensure the structural stability and safety of the product. If the compressive strength of the entire core is too high, when elemental red phosphorus expands, severe stress will occur inside the material, causing damage to the internal structure of the material, exposing the elemental red phosphorus, and even causing damage to the SEI film on the surface of the negative electrode, seriously weakening its electrochemical performance when acting as a negative electrode material. In addition, when the etching degree is too high, part of the red phosphorus may be exposed to the environment, and the performance will also be weakened.

[0055] In addition to etching treatment, technicians in this field can also choose other methods to regulate the powder compressive strength of the phosphorus-carbon composite material, which is not limited to the above methods. For example, technicians in this field can directly choose a graphite material with a porous structure as the core component.

[0056] In some embodiments, the shell further comprises a carbon material, and the mass content of the fast ion conductor in the shell is 20-50%.

[0057] Further preferably, the shell further comprises carbon material, and the mass content of the fast ion conductor in the shell is 25-35%.

[0058] Under the condition of a certain thickness, if the proportion of the fast ion conductor in the shell is too small, it will not significantly improve the conductivity and cycle performance of the overall product. However, if the proportion is too large, it will not only affect the adhesion strength of the fast ion conductor on the shell, but also affect the volume effect restriction of the shell on the elemental red phosphorus in the core. When the content of the fast ion conductor in the shell is set within the above preferred range, the electrochemical performance of the obtained product is better.

[0059] In some embodiments, the phosphorus-carbon composite material is prepared by the following method:

[0060] (1) providing a graphite material, etching the graphite material, and then loading elemental red phosphorus on the graphite material to obtain a core mixture;

[0061] (2) preparing a shell mixture, wherein the shell mixture includes a fast ion conductor, a carbon material or a precursor thereof;

[0062] (3) The core mixture and the shell mixture are uniformly mixed and calcined to obtain the phosphorus-carbon composite material.

[0063] In some embodiments, the graphite material includes at least one of artificial graphite and natural graphite.

[0064] In some embodiments, the etching process is performed at a temperature of 100 to 150° C. and for a time of 1 to 5 hours.

[0065] In some embodiments, the elemental red phosphorus is supported on the graphite material by vaporization and condensation processes.

[0066] In some embodiments, the shell mixture includes a fast ion conductor and a carbon material precursor.

[0067] Compared with the use of ready-made carbon materials and fast ion conductors, the use of precursor materials with certain adsorbability such as asphalt, organic polymers, biomass, etc. and pre-compounded with fast ion conductors can achieve better uniform dispersion and coating integrity of the inner core. According to actual needs, technical personnel in this field can also use other common ready-made carbon materials and adopt other methods to prepare the shell mixture. For example, ready-made organic matter is compounded with certain carbon fibers to prepare a precursor solution, and then electrospinning or CVD is used to compound it with a fast ion conductor to finally prepare a shell mixture. As long as the set effect of the final product can be achieved, there is no restriction.

[0068] Specifically, the carbon material precursor includes pitch.

[0069] In some embodiments, the mass ratio of the asphalt to the fast ion conductor is (2-5):1.

[0070] Specifically, the mass ratio of the asphalt to the fast ion conductor is in the range of one or any two of 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, and 5:1.

[0071] In some embodiments, the mass ratio of the asphalt to the fast ion conductor is (3-4):1.

[0072] Asphalt has high adhesion and can effectively achieve mutual dispersion when mixed with fast ion conductors as a precursor. At the same time, the resulting shell mixture can also achieve excellent coating integrity and stability for the core mixture, and will not delaminate or fall off during the subsequent calcination process. In addition, the asphalt contains rich doping elements such as N elements. Compared with pure carbon materials, the carbon materials obtained after calcining asphalt have better electrochemical properties. In the process of preparing the shell, the controllability of the fast ion conductor content in the shell in the final product based on the mass ratio of asphalt to fast ion conductor is higher.

[0073] In some embodiments, the mass ratio of the core mixture to the shell mixture is 10:(0.1-3).

[0074] In some embodiments, the temperature during the calcination treatment is 800-1000° C., the time is 12-18 hours, and the heating rate during the calcination treatment is 8-12° C. / min.

[0075] In a specific embodiment, the technical solution of the present application further provides a negative electrode plate, including a negative electrode active layer, wherein the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes the phosphorus-carbon composite material described in the present application.

[0076] In a specific embodiment, the technical solution of the present application also provides a secondary battery, including the negative electrode plate described in the present application.

[0077] In some embodiments, the secondary battery includes a positive electrode sheet.

[0078] In some embodiments, the positive electrode plate includes a current collector, a positive electrode material layer disposed on the current collector, the positive electrode material layer includes a positive electrode material, and the mass content of the positive electrode material in the positive electrode material layer is 95-97%.

[0079] In some embodiments, the positive electrode material includes at least one of lithium iron phosphate material, lithium cobalt oxide material, lithium nickel cobalt manganese oxide material, and lithium manganese iron phosphate material.

[0080] In some embodiments, the positive electrode material layer further includes at least one of a conductive agent and a binder.

[0081] Further preferably, the binder includes at least one of polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.

[0082] Further preferably, the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0083] In some embodiments, the thickness of the positive electrode material layer is 70 to 150 μm.

[0084] In some embodiments, the negative electrode plate further includes a current collector, and the mass content of the negative electrode material in the negative electrode material layer is 95-98%.

[0085] In some embodiments, the negative electrode material layer further includes at least one of a conductive agent and a binder.

[0086] Further preferably, the binder includes at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl butyral, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, and polyvinyl alcohol.

[0087] Further preferably, the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0088] In some embodiments, the thickness of the negative electrode material layer is 50 to 150 μm.

[0089] Based on the special structural design of the phosphorus-carbon composite material described in the present application, when used in secondary batteries as negative electrode materials, both the corresponding matching positive electrode materials and the composite components used in the preparation of the pole pieces have high universality. Technicians in this field can select different positive electrode materials and corresponding components to prepare pole pieces according to actual application requirements, and the expected electrochemical performance effects can be achieved.

[0090] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:

[0091] Example 1

[0092] A phosphorus-carbon composite material and a preparation method and application thereof. The preparation method of the phosphorus-carbon composite material comprises the following steps:

[0093] (1) adding 100 g of artificial graphite with an average particle size of 12 μm into 200 mL of 18 wt % KOH solution, stirring and soaking and etching at 100° C. and 300 rpm for 18 h, washing with deionized water, and drying to obtain an etched graphite material;

[0094] (2) Using a vacuum multi-temperature zone tubular furnace, red phosphorus was placed in the left heating zone of the instrument, the temperature was controlled at 450°C, and the etched graphite was placed in the right heating zone, the temperature was controlled at 265°C, the control time was 5 hours, and the elemental red phosphorus was loaded by the steam-condensation method to obtain a core mixture; the mass ratio of the etched graphite material to the elemental red phosphorus was controlled to be 20:2;

[0095] (3) mixing asphalt and Li6Ce8Ti(PO4)6 in a mass ratio of 3:1 to prepare a shell mixture;

[0096] (4) The core mixture and the shell mixture were mixed in a mass ratio of 10:1, and then heated to 900° C. at a rate of 10° C. / min in a nitrogen environment and calcined for 15 h to obtain a phosphorus-carbon composite material. The structure is as follows Figure 1 As shown, the green shell layer is well coated on the black graphite material and the red elemental red phosphorus surface loaded on the graphite material to form a core-shell structure, and the electron microscope image of the material is as follows Figure 2 and 3 As shown, it can be seen that the particles of the obtained product have good dispersion, no obvious agglomeration phenomenon, and a relatively smooth surface. The etched graphite material is observed by electron microscope, as shown in Figure 4 As shown, it can be seen that although the size is similar to the final product, there are more holes on the graphite surface after etching, and the morphology is quite different from the final product.

[0097] The phosphorus-carbon composite material was characterized and the results are shown in Table 1.

[0098] Example 2

[0099] A phosphorus-carbon composite material and a preparation method and application thereof, which differs from Example 1 only in that in step (2), the mass ratio of the etched graphite material to the elemental red phosphorus is controlled to be 20:2.5.

[0100] Example 3

[0101] A phosphorus-carbon composite material and a preparation method and application thereof, which differs from Example 1 only in that in step (2), the mass ratio of the etched graphite material to the elemental red phosphorus is controlled to be 20:3.

[0102] Example 4

[0103] A phosphorus-carbon composite material and a preparation method and application thereof, which differs from Example 1 only in that in step (2), the mass ratio of the etched graphite material to the elemental red phosphorus is controlled to be 20:1.

[0104] Example 5

[0105] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that in step (3), asphalt and Li6Ce8Ti(PO4)6 are mixed in a mass ratio of 4:1.

[0106] Example 6

[0107] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 being that in step (3), asphalt and Li6Ce8Ti(PO4)6 are mixed in a mass ratio of 5:1.

[0108] Example 7

[0109] A phosphorus-carbon composite material and its preparation method and application, which differs from Example 1 only in that in step (3), asphalt and Li6Ce8Ti(PO4)6 are mixed in a mass ratio of 2:1.

[0110] Example 8

[0111] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that in step (4), the core mixture and the shell mixture are mixed in a mass ratio of 10:1.5.

[0112] Example 9

[0113] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that in step (4), the core mixture and the shell mixture are mixed in a mass ratio of 10:2.

[0114] Example 10

[0115] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that in step (4), the core mixture and the shell mixture are mixed in a mass ratio of 10:3.

[0116] Embodiment 11

[0117] A phosphorus-carbon composite material and a preparation method and application thereof, which differs from Example 1 only in that the immersion etching temperature in step (1) is 115° C. and the time is 18 hours.

[0118] Example 12

[0119] A phosphorus-carbon composite material and a preparation method and application thereof, which differs from Example 1 only in that the immersion etching temperature in step (1) is 85° C. and the time is 18 hours.

[0120] Embodiment 13

[0121] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that the average particle size of the artificial graphite in step (1) is 9 μm.

[0122] Embodiment 14

[0123] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that the average particle size of the artificial graphite in step (1) is 15 μm.

[0124] Comparative Example 1

[0125] A composite material and a preparation method and application thereof. The preparation method of the composite material comprises the following steps:

[0126] (1) adding 100 g of artificial graphite with an average particle size of 12 μm into 200 mL of 18 wt % KOH solution, stirring and soaking and etching at 100° C. and 300 rpm for 18 h, washing with deionized water, and drying to obtain an etched graphite material, which is used as a core mixture;

[0127] (2) preparing a shell mixture by mixing commercially available asphalt and Li6Ce8Ti(PO4)6 in a mass ratio of 3:1;

[0128] (3) The core mixture and the shell mixture were mixed in a mass ratio of 10:1, and then the temperature was raised to 900°C at a rate of 10°C / min in a nitrogen environment and calcined for 15 h to obtain a composite material.

[0129] Comparative Example 2

[0130] A phosphorus-carbon composite material and a preparation method and application thereof. The preparation method of the phosphorus-carbon composite material comprises the following steps:

[0131] (1) adding 100 g of artificial graphite with an average particle size of 12 μm into 200 mL of 18 wt % KOH solution, stirring and soaking and etching at 100° C. and 300 rpm for 18 h, washing with deionized water, and drying to obtain an etched graphite material;

[0132] (2) In a vacuum multi-temperature zone tubular furnace of Shanghai Bona Thermoelectric Furnace Co., Ltd., red phosphorus was placed in the left heating zone of the instrument, the temperature was controlled at 450°C, and the etched graphite was placed in the right heating zone, the temperature was controlled at 265°C, the control time was 5 hours, and the elemental red phosphorus was loaded by the steam-condensation method to obtain a core mixture; the mass ratio of the etched graphite material to the elemental red phosphorus was controlled to be 20:2;

[0133] (3) using commercially available asphalt as the shell mixture;

[0134] (4) The core mixture and the shell mixture were mixed in a mass ratio of 10:1, and then the temperature was raised to 900°C at a rate of 10°C / min in a nitrogen environment and calcined for 15 h to obtain a phosphorus-carbon composite material.

[0135] Comparative Example 3

[0136] A phosphorus-carbon composite material and a preparation method and application thereof. The preparation method of the phosphorus-carbon composite material comprises the following steps:

[0137] (1) Using a vacuum multi-temperature zone tube furnace produced by Shanghai Bona Thermoelectric Furnace Co., Ltd., red phosphorus was placed in the left heating zone of the instrument, the temperature was controlled at 450°C, artificial graphite with an average particle size of 12 μm was placed in the right heating zone, the temperature was controlled at 265°C, the control time was 5 hours, and elemental red phosphorus was loaded by the steam-condensation method to obtain a core mixture; the mass ratio of artificial graphite to elemental red phosphorus was 20:2;

[0138] (2) preparing a shell mixture by mixing commercially available asphalt and Li6Ce8Ti(PO4)6 in a mass ratio of 3:1;

[0139] (3) The core mixture and the shell mixture were mixed in a mass ratio of 10:1, and then the temperature was raised to 900°C at a rate of 10°C / min in a nitrogen environment and calcined for 15 h to obtain a phosphorus-carbon composite material.

[0140] Comparative Example 4

[0141] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that the average particle size of the artificial graphite in step (1) is 6 μm.

[0142] Comparative Example 5

[0143] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 is only that the average particle size of the artificial graphite in step (1) is 17 μm.

[0144] Comparative Example 6

[0145] A phosphorus-carbon composite material and a preparation method and application thereof, which differs from Example 1 only in that the immersion etching temperature in step (1) is 125° C. and the time is 24 hours.

[0146] Comparative Example 7

[0147] A phosphorus-carbon composite material and its preparation method and application, the difference from Example 1 is only that the Li6Ce8Ti(PO4)6 is replaced by TiNb2O7.

[0148] Comparative Example 8

[0149] A phosphorus-carbon composite material and a preparation method and application thereof, the difference from Example 1 being that the Li6Ce8Ti(PO4)6 is replaced by lithium titanate.

[0150] The phosphorus-carbon composite material was characterized and the results are shown in Table 1.

[0151] Table 1

[0152]

[0153]

[0154] In order to verify the application effect of each phosphorus-carbon composite material, the phosphorus-carbon composite material is used to prepare a lithium-ion secondary battery, and the steps are as follows:

[0155] Preparation of positive electrode:

[0156] The average particle size of LiNi is 12 μm. 0.5 Co 0.2 Mn 0.3 O2, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed in NMP solvent at a mass ratio of 97:2:1 to prepare a slurry, which was coated on the current collector aluminum foil, dried, cold pressed, and slit to obtain a positive electrode sheet. The thickness of the positive electrode material layer on the sheet was 71 μm.

[0157] Preparation of negative electrode sheet:

[0158] The phosphorus-carbon composite material obtained in each embodiment or comparative example, a mixture of conductive agent SP and CNT (mass ratio 0.45:0.05), and a mixture of binder SBR and PAALi (mass ratio 0.5:1.8) were mixed in NMP solvent at a mass ratio of 97.7:1.1:1.2 to prepare a slurry, coated on a current collector copper foil, dried, cold pressed, and slit to obtain a negative electrode sheet, and the thickness of the negative electrode material layer on the sheet was 81 μm.

[0159] Diaphragm: Use commercially available PE diaphragm.

[0160] Preparation of electrolyte:

[0161] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0162] Preparation of secondary batteries:

[0163] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order and then wound. The obtained electrode assembly is placed in a packaging shell and injected with electrolyte and packaged to obtain the secondary battery.

[0164] Each lithium-ion secondary battery was then tested as follows:

[0165] (1) RT lithium precipitation test:

[0166] RT2.8C / 0.7C lithium plating: ① Charge to 4.5V at 2.8C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.8C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ⑤ Disassemble the interface;

[0167] RT2.6C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.6C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.6C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ⑤ Disassemble the interface;

[0168] RT2.4C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.4C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.4C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ⑤ Disassemble the interface;

[0169] RT2.6C2C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.2C constant current and constant voltage, cutoff rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; Repeat steps ① to ② 49 times in total; ④ Charge to 4.5V at 2.2C constant current and constant voltage, cutoff rate 0.025C, and leave for 5min; ⑤ Disassemble the interface.

[0170] Record the lithium precipitation situation under each condition.

[0171] (2) Cyclic stability test:

[0172] ① Charge the secondary battery to 4.5V at 0.5C at 25℃, with a cut-off current of 0.05C, and leave it for 5 minutes;

[0173] ②Measure the discharge capacity of the secondary battery at this time, recorded as D0;

[0174] ③Discharge the secondary battery at 0.8C to 3V and leave it for 5 minutes;

[0175] ④ Charge the secondary battery to 4.5V at 1.5C, with a cut-off current of 0.05C, and leave it for 5 minutes;

[0176] ⑤ Repeat the above steps ③ to ④ for 400 times, and then measure the discharge capacity of the secondary battery at this time, which is recorded as D1;

[0177] Record the gram capacity, first efficiency and cycle retention rate of the secondary battery % = D1 / D0*100%

[0178] (3) Cyclic secondary battery thickness stability test:

[0179] ① Charge the secondary battery to 4.5V at 0.5C at 25℃, with a cut-off current of 0.05C, and leave it for 5 minutes;

[0180] ②Measure the overall thickness of the secondary battery at this time, recorded as d0;

[0181] ③Discharge the secondary battery at 0.8C to 3V and leave it for 5 minutes;

[0182] ④ Charge the secondary battery to 4.5V at 1.5C, with a cut-off current of 0.05C, and leave it for 5 minutes;

[0183] ⑤ Repeat the above steps ③ to ④ for 300 times, and then measure the overall thickness of the secondary battery at this time, which is recorded as d1;

[0184] Record the cycle thickness change rate of the secondary battery % = (d1-d0) / d0*100%;

[0185] (4) Low temperature discharge performance test:

[0186] Under the condition of 25℃, each secondary battery was first charged to 4.53V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C, then left for 5 minutes, and then discharged at 0.2C constant current, with a cut-off voltage of 3V. The discharge capacity obtained by the test was the initial capacity; then the following operations were performed:

[0187] (1) Shelf time: 5 minutes;

[0188] (2) Temperature box configuration: temperature 25℃;

[0189] (3) Shelf time: 120 min;

[0190] (4) Charge to 4.5V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C;

[0191] (5) Shelf: 5 min;

[0192] (6) Temperature box configuration: temperature -10℃;

[0193] (7) Shelf: 120 min;

[0194] (8) Discharge at a constant current of 0.2C, with a cut-off voltage of 3.2V;

[0195] (9) Shelf: 5 min;

[0196] (10) Temperature box configuration: temperature 25°C;

[0197] (11) Shelf: 120 min;

[0198] (12) Charge to 4.5V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C;

[0199] (13) Shelf: 5 min;

[0200] (14) Temperature box configuration: temperature -20℃;

[0201] (15) Shelf: time 120mi;

[0202] (16) Discharge at a constant current of 0.2C, with a cut-off voltage of 3.2V;

[0203] (17) Shelf: 5 min;

[0204] (18) Temperature box configuration: temperature 25°C;

[0205] (19) Shelf: time 120 min;

[0206] (20) Charge to 4.50 V at 0.5 C constant current and constant voltage, with a cut-off rate of 0.02 C;

[0207] (21) Shelf: 5 min;

[0208] (22) End;

[0209] The above steps obtain the low-temperature discharge capacity of the secondary battery at -10°C and -20°C, and the low-temperature discharge retention rate (%) of the secondary battery = low-temperature discharge capacity / initial discharge capacity.

[0210] The test results are shown in Tables 2 and 3.

[0211] Table 2

[0212] performance 2.2C lithium precipitation 2.4C lithium precipitation 2.6C lithium precipitation 2.8C lithium precipitation Example 1 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 2 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 3 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 4 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 5 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 6 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 7 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 8 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 9 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 10 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Embodiment 11 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 12 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Embodiment 13 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Embodiment 14 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Comparative Example 1 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Comparative Example 2 No lithium precipitation Slight lithium deposition Lithium Separation Severe lithium deposition Comparative Example 3 No lithium precipitation No lithium precipitation No lithium precipitation Slight lithium deposition Comparative Example 4 No lithium precipitation No lithium precipitation No lithium precipitation Slight lithium deposition Comparative Example 5 No lithium precipitation No lithium precipitation Slight lithium deposition Lithium Separation Comparative Example 6 No lithium precipitation Slight lithium deposition Lithium Separation Severe lithium deposition Comparative Example 7 No lithium precipitation No lithium precipitation Slight lithium deposition Slight lithium deposition Comparative Example 8 No lithium precipitation No lithium precipitation No lithium precipitation Slight lithium deposition

[0213] Table 3

[0214]

[0215]

[0216] It can be seen from Tables 2 and 3 that the secondary battery described in the present application has ideal electrochemical properties. During the test cycle, no lithium precipitation phenomenon occurs at the highest rate of 2.8C. At the same time, the gram capacity is high (above 450mAh / g), the initial efficiency is high (above 80%) during the charge and discharge process, and the cycle stability is good (the capacity retention rate can reach more than 77% after 400 cycles). The thickness change rate of the battery during the cycle is low (less than 15%), and it also has ideal low-temperature performance (the discharge capacity retention rate at -10°C is more than 80%, and -20°C is more than 75%). Compared with the comparative example 1 product of the non-phosphorus-carbon composite material, its gram capacity is significantly improved, and compared with the comparative examples 2 and 3 products of the structural design not described in the present application, it has ideal electrochemical performance stability and safety.

[0217] According to the comparison of product performance in Examples 1 to 4, it can be seen that in the inner core, the mass ratio of graphite material and elemental red phosphorus will directly affect the gram capacity and cycle performance of the product. When the ratio of the two is preferably in the range of 20: (2 to 2.5), the resulting secondary battery can better balance the above performances, so that they are all at a higher level.

[0218] According to Examples 1 and 5 to 7, it can be seen that when the content of the fast ion conductor in the shell changes due to a change in the proportion of raw materials during preparation, the gram capacity and first efficiency of the product do not change significantly, but the cycle stability and low-temperature performance of the product do change to a certain extent. Whether the content of the fast ion conductor is too high or too low, it cannot be maintained at the optimal level. After comparison, it was found that when the content of the fast ion conductor in the shell is preferably in the range of 25 to 35%, the corresponding phosphorus-carbon composite material can achieve the best comprehensive performance when applied to the negative electrode material of a secondary battery.

[0219] It can be seen from Examples 1 and 8 to 10 that the ratio of raw material addition of the core and shell layers directly affects the thickness of the shell layer, and further affects the main performance of the product. When the thickness of the shell layer is preferably in the range of 30 to 70 nm, the comprehensive performance of the product is obviously better.

[0220] According to Example 1, Examples 11 to 12, Comparative Example 3 and Comparative Example 6, it can be seen that the looseness and porosity of the graphite material as the main skeleton will change after being etched under different conditions, which will lead to changes in the powder compressive strength of the overall material. When the strength is low, its own compressive strength is insufficient, it is difficult to achieve good structural stability, and the electrochemical performance is naturally poor. As shown in Comparative Example 3, the capacity retention rate of the product after cycling is only 66%, but if the strength is too high, it may cause excessive mutual stress inside the material, resulting in the stress of the elemental red phosphorus not being released after a certain period of expansion / contraction, and even the red phosphorus being exposed, which is not conducive to long-term structural stability. As shown in Comparative Example 6, the performance of the product also cannot reach the ideal level.

[0221] According to the comparison of the products of Example 1, Examples 13 to 14 and Comparative Examples 4 to 5, it can be seen that the particle size of the graphite material has a great influence on the particle size of the overall product. When the particles of the graphite material are too large or too small, the composite particles in the obtained product cannot well balance the inhibitory effect on the volume effect of elemental red phosphorus and the dispersibility of the overall particles, and the electrochemical performance of the product is naturally low. Only when the average particle size of the product described in the present application is maintained at 9 to 16 μm, the product can achieve ideal cycle performance and low-temperature performance, and at the same time have a higher gram capacity.

[0222] In addition, according to Comparative Examples 7 and 8, it can be seen that when different fast ion conductors are used to prepare phosphorus-carbon composite materials, in addition to causing differences in the cycle performance and capacity of the products, the safety performance is also different. Products prepared with inappropriate fast ion conductors may cause lithium precipitation.

[0223] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of this article rather than to limit the scope of protection of this article. Although the present application is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of this article can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of this article.

Claims

1. A phosphorus-carbon composite material, characterized in that: comprising a composite particle, the composite particle comprising a core and an outer shell; The core comprises graphite material and elemental red phosphorus; The housing includes a fast ion conductor; The fast ion conductor includes Li 3y Ce 14-3y Ti(PO4)6, 1≤y≤4; The average particle size of the phosphorus-carbon composite material is 9 to 16 μm, and the powder compressive strength under a pressure of 5 T is 1.85 to 1.92 g / cm 3 .

2. The phosphorus-carbon composite material according to claim 1, characterized in that: The ratio of the thickness of the inner core to that of the outer shell is (500-1000):1; preferably, the thickness of the outer shell is ≤100 nm.

3. The phosphorus-carbon composite material according to claim 1, characterized in that: The mass ratio of the graphite material to the elemental red phosphorus in the inner core is 20:(1-3).

4. The phosphorus-carbon composite material according to claim 1, characterized in that: The shell also includes carbon material, and the mass content of the fast ion conductor in the shell is 20-50%.

5. The phosphorus-carbon composite material according to claim 1, characterized in that: The phosphorus-carbon composite material is prepared by the following method: (1) providing a graphite material, etching the graphite material, and then loading elemental red phosphorus on the graphite material to obtain a core mixture; (2) preparing a shell mixture, wherein the shell mixture includes a fast ion conductor, a carbon material or a precursor thereof; (3) The core mixture and the shell mixture are uniformly mixed and calcined to obtain the phosphorus-carbon composite material.

6. The phosphorus-carbon composite material according to claim 5, characterized in that: The carbon material precursor includes asphalt; the mass ratio of the asphalt to the fast ion conductor is (2-5):

1.

7. The phosphorus-carbon composite material according to claim 5, characterized in that: The mass ratio of the core mixture to the shell mixture is 10:(0.1-3).

8. A negative electrode plate, characterized in that: It comprises a negative electrode active layer, wherein the negative electrode active material layer comprises a negative electrode material, and the negative electrode material comprises the phosphorus-carbon composite material according to any one of claims 1 to 7.

9. A secondary battery comprising the negative electrode sheet according to claim 8.

10. An electrical device, characterized in that: It comprises the secondary battery as claimed in claim 9, and the secondary battery is used as a power supply for the electrical device.